Association Between Severity Grading Score And Acute Phase Reactants In Patients With Crimean Congo Hemorrhagic Fever. (17th November 2021) - Bozkurt, Ilkay; Esen, Saban
ABSTRACT: As the COVID-19 pandemic continues, countries still have to struggle with their endemic diseases such as Crimean-Congo hemorrhagic fever (CCHF). Severity grading score (SGS) is a practical approach and may shed light on the course of the CCHF, whose pathogenesis is not clearly understood, and have no effective treatments. It is aimed to assess the association between SGS and acute phase reactants (APR). Laboratory-confirmed patients were categorized by severity scores, and the relationship between APR and SGS was evaluated. A significant correlation between SGS and C-reactive protein (CRP) was found ( p < 0.001). High SGS was associated with mortality and high CRP levels were used to predict the mortality at the beginning of the hospital admission. To predict the outcome of the disease and for appropriate patient management, SGS and APR can be used simultaneously.